Characterization of human, mouse, and rat cultures of enteric glial cells and their effect on intestinal epithelial cells. Issue 11 (29th August 2013) - Soret, R.; Coquenlorge, S.; Cossais, F.; Meurette, G.; Rolli‐Derkinderen, M.; Neunlist, M.
Abstract Background Enteric glial cells (EGC) are major regulators of neuronal and intestinal epithelial cell (IEC) functions. Simple isolation methods of EGC, especially human tissues, remain scarce and limit their study. We present herein a method to isolate EGC and we characterize EGC phenotype and their functional impact on IEC. Methods Longitudinal muscle and myenteric plexus preparations of rat, mouse, or human intestine were obtained by microdissection. After mechanical and enzymatic dissociation, individual ganglionic or interganglionic structures were seeded into plates, maintained in culture several weeks and passaged up to 4 times. Purity of cultures was assessed by immunocytochemistry using antibodies against glial fibrillary acidic protein (GFAP), S100β and Sox10 or smooth muscle actin. Effects of adenosine triphosphate (ATP) on intracellular Ca2+ signaling in EGC were studied. Co‐cultures of EGC with IEC line, Caco‐2, were performed for 2–6 days to analyze their impact on monolayer resistance, cell proliferation, and cell spreading. Key Results More than 80% of DAPI‐positive cells were GFAP, S100β, and Sox10‐immunoreactive. EGC expressed these glial markers over 4 consecutive passages, and the majority of them responded to ATP by an increase in intracellular Ca2+ concentration. In addition, rat, mouse, and human EGC increased intestinal barrier resistance, IEC size, and reduced IEC number. Conclusions & Inferences We have developed a simple method to isolate and culture human, rat, or mouse EGC. EGC exhibit similar functional properties on the intestinal barrier independently of the species. This study sets the basis for exploring glial biology and functions in human health and diseases.